Fatores para atração e retenção de pessoas no setor privado: estudo de caso em uma empresa do ramo de transporte de pessoas - Gurgacz, Assis Marcos (2019)
This work aimed at identifying factors that attract and keep people in a private company within the transport industry, with views to contribute with information available in academic, professional and scientific literature on the theme; also determining factors and ideas that may offer a base to develop an employee value proposition to be implemented in the company. For that end, we performed a qualitative research using a study group – with focus-group style meetings – and employee-requested termination questionnaire files as data sources. Data analysis showed that the main attraction factors of the company are: friend referral and prior experience in the same company (due to its good reputation along over 50 years in the marketplace); search for new experiences/work opportunities and employment needs/only option (due to the company offering first job opportunities and for being open to people with no experience in the company’s industry). The main factors influencing employee retention are the organizational procedures in the workplace and the monthly compensation, minding that compensation up sides and downsides were also noted. Monthly compensation did not have much influence in employee retention while they were in a work group. On the other hand compensation was mentioned as a stimulus factor for requiring termination. Based on identifying that factor, the company developed an employee value proposition to be implemented and intends on continuing the proposition cycle, performing its communication, integration and measurements continuously.